Not too costly, after all: an examination of the inflated cost-estimates of health, safety and environmental protections (Washington, DC, 1994)
"Federal agencies frequently overestimate the costs of their regulations. They often use poor quality data, conservative assumptions, and static analysis. Overestimates emerge — be it from OSHA’s analysis of the costs of a proposed Vinyl Chloride Standard, EPA’s regulation of acid rain, NHTSA’s regulation of test procedures for advanced air bags, FDA’s efforts to reduce the risk of an outbreak of transmissible spongiform encephalopathis, or CPSC’s cost estimate for flammable upholstered furniture. Despite concerns of industry with cost and feasibility before a standard is promulgated, the paths toward compliance predictably lead to lower cost alternatives, often far lower than predicted. Sometimes regulatory compliance even promotes increases in productivity."